Early migraine intervention with sumatriptan 100 mg in patients with a history of nonresponse to sumatriptan 50 mg: an open-label, prospective study of multiple attacks - Landy, Stephen (Elsevier, 2004)
BACKGROUND: Early treatment with sumatriptan tablets (50 and 100 mg) has been shown to be effective in retrospective and prospective study designs. Despite the efficacy of sumatriptan 50 mg and early intervention, however, some patients continue not to respond completely to this dose. New evidence with a scientific basis for early intervention suggests that some patients may need to treat early to prevent the establishment of central sensitization. Also, patients cite complete pain relief as the most important attribute of a migraine medication. OBJECTIVE: The primary objective of this study was to determine the 2-hour efficacy of sumatriptan 100 mg in achieving complete pain relief in patients with a history of nonresponse to sumatriptan 50 mg in an early-intervention treatment paradigm. Secondary end points included complete pain relief at 4 hours, consistency of complete relief in at least 2 of 3 attacks, sustained complete relief over 24 hours, satisfaction with the 100-mg dose, and relief of associated symptoms. METHODS: This open-label, prospective study was conducted at the Wesley Headache Clinic (Memphis, Tennessee). Male and female patients between the ages of 18 and 65 years who fulfilled International Headache Society classification criteria for migraine, and who had a documented history of nonresponse to sumatriptan 50 mg at 2 hours after dosing when treating in the early, mild-pain phase in at least 2 of 3 migraine attacks were eligible for the study. Patients were instructed to receive one 100-mg sumatriptan tablet at the earliest sign of pain, while still mild, in 3 subsequent migraine attacks. After each treated attack, patients were to record a detailed diary entry. RESULTS: Twenty patients (17 women, 3 men; mean age, 44 years) treated all 3 migraines during the early, mild-pain phase and completed the study. Of the 60 attacks treated, 48 (80%) were pain free at 2 hours, 56 (93%) were pain free at 4 hours, and 45 (75%) were pain free at 2 hours and continued to be pain free at 24 hours (sustained pain-free response). Sumatriptan 100 mg was well tolerated; none of the patients reported any adverse events. CONCLUSIONS: In this study of migraineurs with a history of nonresponse to sumatriptan 50 mg at 2 hours after dosing in the early, mild-pain phase of migraine, increasing the dose of sumatriptan from 50 mg to 100 mg in the early-intervention paradigm, in most attacks complete pain relief was achieved for up to 24 hours. Because patients have indicated that becoming pain free was their therapeutic goal, based on the results of this study, physicians may want to consider increasing the dose of sumatriptan to 100 mg at the first sign of pain if the patient has consistently not responded to sumatriptan 50 mg in the early-intervention model.